2006
DOI: 10.2298/avb0603235i
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between total iron binding capacity and transferrin concentration in neonatal piglets treated with iron-dextran

Abstract: Serum iron concentration and iron saturation of transferrin (Trf) are measures of body iron stores after administration of iron supplements. In clinical and experimental research, the complex determination of Trf was replaced by the simple determination of total iron binding capacity (TIBC). The objective of this work was to define if TIBC could be an adequate measure for Trf in neonatal piglets after i.m. iron administration. Treated piglets received 150 mg of iron-dextran i.m. the first day of life, and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For this reason, TIBC is considered as an indirect measure of Tf concentration. While a small number of studies have been found related with Tf level (Thoren-Tholling and Martinsson, 1974;Lampreave and Pineiro, 1992;Ilic et al, 2006), many other researchers (Kozat et al, 2006;Eltain 2008;Merhan and Ozcan, 2010;AL-Dujaily and AL-Hadithy, 2014) prefer to use the TSAT value in their study.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, TIBC is considered as an indirect measure of Tf concentration. While a small number of studies have been found related with Tf level (Thoren-Tholling and Martinsson, 1974;Lampreave and Pineiro, 1992;Ilic et al, 2006), many other researchers (Kozat et al, 2006;Eltain 2008;Merhan and Ozcan, 2010;AL-Dujaily and AL-Hadithy, 2014) prefer to use the TSAT value in their study.…”
Section: Discussionmentioning
confidence: 98%